Metabolite Profiling of Kombucha Fermented Beverage with Substrate Variation - Tangapo, Agustina Monalisa; Veralyn Maabuat, Pience; Kolondam, Beivy; Wahyudi, Lalu; Mambu, Susan Marlein; Pasassa, Marsia (Universitas Sam Ratulangi, 2025)
Kombucha is a fermented beverage of tea and sugar with symbiotic culture of bacteria and yeast (SCOBY/symbiotic culture of bacteria and yeast). Changes in chemical composition which are functional constituents and flavor components of kombucha beverages can occur during kombucha fermentation. Substrate is one of the factors determining the characteristics of kombucha. Generally, the substrate used in making kombucha comes from Camellia sinensis tea leaves. Modification of substrates for kombucha fermentation with herbs can increase the various potentials of kombucha. The aim of this study was to analyze untargeted metabolomics for metabolite profiling of kombucha fermented from different substrates (clove leaves, guava leaves, mint leaves, and morel berry leaves). The research methods used were controlled fermentation for fourteen days, and metabolomic analysis using Gas Chromatography-Mass Spectrometry. The results showed that different substrates affected the metabolite content profile of fermented kombucha. The metabolite profile of Gas Chromatography-Mass Spectrometry results identified from clove kombucha as many as 26 metabolites, from guava kombucha 13 metabolites, from mint leaf kombucha 24 metabolites, and morel berry leaf kombucha with 21 metabolites. There is a metabolite identified from each kombucha with these substrate variations, namely 5-Hydroxymethylfurfural.